Using a hardware coprocessor for message scheduling in fieldbus-based distributed systems - Fonseca, José A. (2011)
“Copyright © [2001] IEEE. Reprinted from 8th IEEE International Conference on Electronics, Circuits and Systems. ISBN:0-7803-7057-0. This material is posted here with permission of the IEEE. Internal or personal use of this material is permitted. However, permission to reprint/republish this material for advertising or promotional purposes or for creating new collective works for resale or redistribution must be obtained from the IEEE by writing to pubs-permissions@ieee.org. By choosing to view this document, you agree to all provisions of the copyright laws protecting it.”